Augmentation of modified Alvarado score with abdominal ultrasound in diagnosis of acute appendicitis - Sharma, Shipra; Soni, Ankit; Kumar, Sanjay; Poptani, Manoj (International Surgery Journal, 2020)
Background: Acute appendicitis is one of the commonest surgical emergencies. But confirming the diagnosis of acute appendicitis is still a subjective issue for clinicians. Modified Alvarado score is based on clinical and laboratory findings which is scored upto 9. Management of 5 to 7 modified Alvarado score came under equivocal. Either may be conservative or operative. Methods: We augmented the modified Alvarado score with abdominal ultrasound in diagnosis of acute appendicitis. Results: Outcomes were evaluated in terms of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and negative appendicectomy rate, results of our study are sensitivity 95.7%, specificity is 76.92%, PPV 93.75% and NPV 33.34%. Conclusions: Overall increased sensitivity, specificity, NPV and PPV of the augmented approach is useful for diagnosis of acute appendicitis which scored under 5-7 of modified Alvarado scoring system.